A Straightforward Access to Cyclotriveratrylene Analogues with C1 Symmetry: Toward the Synthesis of Monofunctionalizable Cryptophanes. Issue 47 (19th December 2017) - Milanole, Gaëlle; Gao, Bo; Mari, Emilie; Berthault, Patrick; Pieters, Grégory; Rousseau, Bernard
Abstract : A straightforward and practical access to various C 1 ‐symmetric cyclotriveratrylene derivatives from a monohalogenated cyclotriphenolene is described. This unique scaffold can be used as a precursor for the rapid construction of monofunctionalizable cryptophane‐based biosensors for hyperpolarized 129 Xe MRI. Abstract : A straightforward and practical access to various C 1 ‐symmetric cyclotriveratrylene derivatives from a monohalogenated cyclotriphenolene is described. This unique scaffold can be used as a precursor for the rapid construction of monofunctionalizable cryptophane‐based biosensors for hyperpolarized 129 Xe MRI.